Online Kumustahan: Connecting Teachers, Parents, and Students through Online Communication - Michael Bordeos; Karla Roxanne Lagman; Juliet Manas; Milette Villaraza (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
This study intends to investigate the impact of online kumustahan as a communication platform in providing learners with monitoring and feedback on their learning progress in a modular distance learning mode. In addition, to assess and recommend strategies to improve effective monitoring and feedback between teachers, parents, and students. An online survey was issued to a random sample of 50 Grade 10 students from Bagong Nayon II National High School to collect the data. The studied data and information from the students all agreed with the study's questions. According to the findings, the majority of students still prefer classroom monitoring to online kumustahan due to some issues they face when participating in online kumustahan, such as unstable internet connections and load budgets, decreased communication levels between teachers and students due to limited participants, and increased feelings of isolation due to the fact that not all students participate in online kumustahan. However, this study discovered that online kumustahan has a favorable impact on teachers and students evaluating learning progress. Because the sample was exclusively made up of students, this study only looked at the impact from the perspective of students.